PENGARUH LATIHAN MENENDANG BOLA KE GAWANG SECARA BERGILIRAN TERHADAP KEMAMPUAN SHOOTING U-12 PADA SSB YAPORA PRATAMA PEKANBARU - Lintang Bela Pertiwi; Ramadi Ramadi; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study was conducted to determine whether there is any effect of the practice of kicking the ball on the go in turns to the ability of U-12 shooting on SSB Yapora Pratama Pekanbaru, so that when performing the attack pattern the player is able to create more goals into the opposing goal and can win the game. The problem in this study is that there are still shortcomings during practice. Especially in the final settlement or a ball shot into the opponent's goal. This can be seen from the lack of basic shooting techniques so the ball is easily captured by the opposing goalkeeper. This type of research is a type of experimental research to see the effect of the form of exercise. The purpose of this exercise is to see the effect of the practice of kicking the ball on the go in turn to the ability of U-12 shooting on SSB Yapora Pratama Pekanbaru. The population in this study as many as 43 people, and the sample is only 10 people. Sampling technique is by using probability sample. The data retrieval technique is obtained from pre-test and post-test. Instruments in this research use Shooting Test / Kick Ball to Target (shooting) as a tool to measure shooting skill. Based on statistical data analysis, yield preetest data Lhitung equal to 0,1478 data posttest Lhitung equal to 0,1571 and Lhitung <Ltabel. Then the data is normally distributed. The analysis was performed using the t-test. Based on data analysis and discussion, proven with Thitung of 4.74 and Ttabel of 1.833. Means Thitung > Ttabel. At a significant level α = 0.05. Then it can be concluded that there is a significant influence of the practice of kicking the ball on goal in turns to the ability of U-12 shooting on SSB Yapora Pratama Pekanbaru.Keywords: Kick the Goal in Turn, Shooting Ability, Football